FARM LEVEL EFFICIENCY OF RUBBER AS A PERENNIAL CROP USING COBB-DOUGLASS PRODUCTION FRONTIER - Aliyu, A.; Shelleng, B.A; Usman, J. (International Journal of Research -GRANTHAALAYAH, 2018)
This paper examines the parametric efficiency analysis of rubber production in Malaysia using Stochastic Frontier Analysis (SFA). The 3 different sample sizes used were 307, 206 and 101 for all-age, matured-age and old-age categories respectively. The results of the study reveals that the mean values of the rubber yield under all-age category was 3,638.28kg/ha while that of the matured-age and old-age categories 4,611.34kg/ha and 1,653.61kg/ha respectively. The Maximum likelihood estimates (MLE) results revealed that 5 independent variables were significant under all-age and matured-age categories while the old-age category has all the independent variables significant. With regards to elasticity of production for rubber task, 1% increase in number of rubber tree/ha leads to an increase in 0.76, 0.70 and 0.61 per cents in all-age, matured-age and old-age crop categories respectively. The coefficients values of the sigma squared for the all-age, matured-age and old-age were 0.14, 0.26 and 0.03 respectively, while the gamma values for the respective crops age categories stood at 1.00, 1.00 and 0.5. The coefficients values of all-age crops category showed that 3 variables were statistically significant at 1% level of significance. 2 variables were having negative coefficients while the remaining 1 had positive coefficient. The mean technical efficiency scores for all-age, matured-age and old-age crops categories were found to be respectively 0.70, 0.77 and 0.72. None of the crops age categories have farms on the frontier. The study concludes that Race and marital status were found to be very critical in determining efficiency of all-age crop category. Also, the matured-age crops are better than the other two crop-age categories in terms of efficiency. Also, both the matured-age and the all-age crop categories are experiencing decreasing return to scale of the production process while the old-age category has an increasing return to scale production process. The study recommends downsizing some of the inputs especially farm size, fertilizer application rate as well as farm tools.